Sarcoidosis: an orphan disease needs to be adopted - Jain, Rashi; Mohan, Anant; Kumari, Rinkee; Guleria, Randeep (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Sarcoidosis, a multi-organ granulomatous disorder, continues to remain an elusive entity. Regarding diagnosis of sarcoidosis, clinicians usually lack any confident explanation about disease cause and course.Disease course in sarcoidosis is generally self-limiting but many patients face an uncertain future with chronic illness. Depression, perceived stress, anxiety, fatigue and decreased quality of life are on the higher side in the patients with sarcoidosis. For a disease like sarcoidosis, the disease-specific clinical model might prove beneficial for its management. Unfortunately, we are lacking in such types of models. Multidisciplinary clinical model and in-person support groups may work favorably to cure the disease and to inform the public about the disease so the patients do not go through undue trauma. Although lacking in clinical model, UK and USA both have support and welfare groups that are helping sarcoidosis patients through their education programs, fund raising awareness camps, and other clinical facilities. In India, we also need similar groups so we can make people aware of the disease and its outcomes. Through such organization, we can also assemble clinical and research groups together to find actual prevalence of sarcoidosis and to arrange funds for better research in this field. Extensive research is indeed required to find some breakthroughs which will provide answers to etiology, diagnosis, treatments and a cure for the disease.